Fight club: culture, conflict and everyday life amongst an online 'community'. (21st December 2006) - Fletcher, Gordon; Greenhill, Anita; Campbell, John
This paper examines a specific online community and the degree to which participants' association is constituted and reinforced through conflict. We sample the existing literature regarding online communities in an historical sense and critique the preponderance among these writings to advocate trust and consensus. Our argument is that much of the existing literature has a particular intellectual heritage that has heavily shaped contemporary understandings of online communities. Field examination of the community reveals the use of meaning-laden, often aggressive pseudonyms coupled with conversations that are openly belligerent and more pointedly a lack of general consensus. We conclude with the presentation of a research agenda for this field of research that argues for a nuanced reconnection to more 'traditional' sociological literature where conflict figures heavily.